From Prose to Pas De Deux: Barbie in the Nutcracker (2001) and the Refashioning of The Nutcracker Narrative into a Piece of Barbie’s Legacy - Carrillo, Tatyana (Transcr(é)ation)

(untitled) (Western Libraries, University of Western Ontario, 2025)
The first in a series of Barbie-centered animated adaptations of canonical literature that spanned the early 2000s, Mattel’s Barbie in the Nutcracker stars the company’s eponymous heroine in an adaptation of E.T.A. Hoffmann’s story “The Nutcracker and the Mouse King” and its famous ballet adaptation, The Nutcracker. By centering Barbie as the protagonist, this adaptation exemplifies how an animated revisitation of an oft-adapted story transforms a classic literary text to establish Barbie’s burgeoning twenty-first century transformation from a plastic toy to a moving and talking filmic heroine.Animated with motion-captured choreography from the New York City Ballet, and driven by Barbie’s adventures in a fantastical world, Barbie in the Nutcracker reifies the original story’s historical tethering to its balletic adaptation–which is underscored by the protagonist’s smooth human-like movement as she dances. The production of tie-in dolls at the film’s release also suggests the film’s ultimate purpose as a form of multimedia marketing for the Barbie brand itself. Drawing from Hutcheon’s assertion of adaptation’s pleasurable repetition of the familiar and Henry Jenkins’ construction of transmedia narratives, this paper contends that Barbie in the Nutcracker (2001) shows that Mattel’s animated revisitation of a literary text simultaneously emphasizes the elongated cultural relevance of Hoffmann’s story while that same reconstruction of the text signals the use of Hoffmann’s story to bolster the doll’s jump from toy to screen through animation (Hutcheon, 2013; Jenkins 2006).